Symbolic Violence of Women in Bhayangkari Institution - Ridho Dwie; Sutinah; Septi Ariadi (Universitas Airlangga, 2022)
Bhayangkari organization becomes interesting and relevant to be researched in the perspective of gender, bhayangkari is a cohesive organization, this organization consists of the wives of soldiers and wives of POLRI civil servants who are attached to the culture of the military hierarchy that is still strong. In addition, bhayangkari consists of women with heterogeneous cultural, educational and social status backgrounds. The military hierarchy system of authoritarian leadership, seniority and juniority, and personally targeting surveillance is still a culture within the Bhayangkari organization. This research methodology examines how symbolic violence occurs alive as the wife of a polri member (Bhayangkari) the subject of this study is the administrator and the member of the Bhayangkari organization is a woman, case studies this article focuses on looking at the systems and structural roles performed by Bhayangkari members. The theory of symbolic violence is applied to explain how women are controlled and victims of patriarchal oppression in this organization. The study found that women in Bhayangkari were proud to be controlled and suppressed under the normative role of organizations with patriarchal cultures. This is reflected in the way they are active in the organization and totality in carrying out the work program. Furthermore, the special behavior was carried out to gain the prestige and pride of bhayangkari women. Finally, the study concluded that Bhayangkari women were unaware that symbolic violence practices occurred in their organizations. They don't realize that Patriarchal culture has controlled them and defined them as victims of symbolic violence. In this study is to perform data analysis techniques starting with qualitative analysis of the results of interviews, then doing an in-depth interpretation of the relationship between theory and facts that occur. Here also includes quotes (direct quotations) from informants. The issue of gender, especially in women, has become quite an important issue to study, especially looking at the number of demographic bonuses to come.